ANALISIS FAKTOR KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET FE SELAMA KEHAMILAN - Baska, Dwie yunita; Handika, Renta (LPPM Universitas Sari Mulia, 2025)
Background: According to the World Health Organization (WHO) in 2023, 37% of pregnant women aged 15–49 are affected by anemia. The incidence of anemia among pregnant women in Bengkulu Province remains notably high, with a total of 1,824 individuals affected. A key preventive measure against anemia in pregnant women is the consumption of iron tablets. Objective:. The objective of this study is to identify the factors influencing pregnant women's adherence to the consumption of iron tablets throughout their pregnancy Methods: This research employs a cross-sectional design, encompassing the entire population of pregnant women in their second and third trimesters within the jurisdiction of the Kuala Lempuing Health Center in Bengkulu City from January to May, involving 54 pregnant participants. Subjects were selected via total sampling, and data were collected using a questionnaire, followed by analyses conducted in univariate, bivariate (Chi-Square), and multivariate formats. Result: The bivariate analysis revealed a p-value of less than 0.05 for all variables, indicating a significant relationship between ANC visits, support from healthcare providers, and spousal support in relation to pregnant women’s adherence to iron tablet consumption. Furthermore, the multivariate analysis identified ANC visits as the most dominant influencing factor, with an Exp(B) value of 10.522 Conclusion: The importance of effective counseling concerning the consumption of iron tablets is underscored, focusing on the optimal timing and method for intake, potential side effects, and enhancing the monitoring of iron tablet consumption adherence through the Blood Supplement Tablet (BST) control card for pregnant women documented in the Maternal and Child Health (MCH) book Keywords: Anemia, ANC, Iron Tablets, Healthcare Provider Support, Spousal Support, Adherence.